Features of Criminal Liability of Juvenile Criminals: International Legal and Comparative Analysis - Begaliyev, Yernar N.; Sakhatova, Samal Ye.; Temirova, Aizat Zh.; Paryzkyi, Igor V.; Kuprienko, Vladimir M. (International Journal of Criminology and Sociology, 2022)
The relevance of the problem under study lies in the fact that the criminal liability of juvenile criminals is one of the most difficult areas of criminal law. Minors, given their physiological, mental, and social characteristics, are considered a separate category of criminals, being one of the most vulnerable segments of the population. Therefore, juvenile delinquency manifests itself not only in causing harm to public relations, the personality of the victim, but also directly to the minor, forming antisocial behaviour in the latter's mind. Considering the above, the problem of the specific features of the criminal liability of minors remains relevant today. The purpose of the study is to analyse the criminal liability of minors from an international legal standpoint, as well as to carry out a comparative analysis of the features of the regulation of criminal liability of minors in different countries of the world. To fully explore the subject matter of the study, a set of general scientific and special methods of cognition was used. In particular, the study used the methods of scientific knowledge, system analysis, scientific abstraction, generalisation, comparison, analysis and synthesis, grouping, formalisation, historical and logical analysis. For example, the leading method was the comparison method, which helped to compare the specific features of practice in other countries of the world in criminal liability of minors. The study analyses the features of the criminal liability of minors, in particular the minimum age of criminal liability, differences between countries in this regard, as well as general international standards.